Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper provides a quantitative assessment of the long-term prospects of the Luxembourg pension system and analyzes possible reform options. The results indicate a need to adopt-at an early stage and while the problems are still relatively tractable-measures to dampen the growth of pension expenditure. Otherwise, there is a risk that rising taxes or deficits could have detrimental effects on incentives for work, investment, and innovation, and result in an unsustainable slowdown of economic growth.